Analysis of Recruiter Interest in the International 5-Star Hotel Industry in Jakarta Determines Employee Candidates - Ananda Fortunisa; Zumelin Astiwardhani; Irgi Iryansyah (Journal Research of Social Science, Economics, and Management, 2024)
The recruitment process is often influenced by various factors, both objective and subjective. One interesting factor to study is the influence of physical attractiveness, accent, and dialect of candidates on recruiters' assessments. This study aims to reveal the relationship between physical attractiveness and candidate accent, as well as the role of dialect as a mediator, influencing recruiters' perceptions of job suitability, stereotypes formed, and interest in recruiting. This study uses a quantitative method with a questionnaire distribution technique to recruiters in the 5-star hotel industry located in Jakarta. Data obtained from BPS (2024) shows that there are 37 international 5-star hotels in DKI Jakarta Province. Thus, the population of this study was 37 recruiters from international 5-star hotels in Jakarta. This study distributed questionnaires to the entire population so that the sampling technique was carried out using the census technique. The data collected were analyzed using the SEM PLS technique. The results of the study showed that there was no relationship between physical attractiveness and job suitability. While physical attractiveness has a significant relationship to recruiter stereotypes and interest in recruiting. In addition, it was found that dialect mediates the influence of job candidate access to job suitability, recruiter stereotypes and interest in recruiting.